Making the Desert Bloom: Hannah Arendt and Zionist Discourse. Issue 4 (18th May 2016) - Lederman, Shmuel
Abstract: This article discusses an aspect of Hannah Arendt's treatment of the conflict between the Zionists and the Palestinians that has thus far been overlooked in scholarship: her justification of Zionism through the achievements of the Jewish pioneers in cultivating the land, in contrast to the Palestinians' failure to do so. The inability of natives to cultivate their land was a familiar argument in the history of colonialism, used to legitimize the colonialists' right to settle a land and often to displace the natives. How should we understand Arendt's use of this argument? I show that Arendt's argument should be understood in the context of, first, the recurrence of this argument in Western political thought and practices. Second, the Zionists'—Arendt included—need of legitimizing Jewish settlements in Palestine. And third, the influence of Arendt's own political philosophy on her understanding of culture in general, and Palestinian culture in particular.